Controllable nanoscale inverted pyramids for highly efficient quasi-omnidirectional crystalline silicon solar cells. (4th December 2017) - Haiyuan, Xu; Sihua, Zhong; Yufeng, Zhuang; Wenzhong, Shen
Abstract: Nanoscale inverted pyramid structures (NIPs) have always been regarded as one of the paramount light management schemes to achieve extraordinary performance in various devices, especially in solar cells, due to their outstanding antireflection ability with relative lower surface enhancement ratio. However, current approaches to fabricating NIPs are complicated and not cost-effective for massive cell production in the photovoltaic industry. Here, controllable NIPs are fabricated on crystalline silicon (c-Si) wafers by Ag-catalyzed chemical etching and alkaline modification, which is a preferable all-solution-processed method. Through applying the NIPs to c-Si solar cells and optimizing the cell design, we have successfully achieved highly efficient textured solar cells with NIPs of a champion efficiency of 20.5%. Significantly, these NIPs are further demonstrated to possess a quasi-omnidirectional property over broad sunlight incident angles of approximately 0°–60°. Moreover, NIPs are theoretically revealed to offer light trapping advantages for ultrathin c-Si solar cells. Hence, NIPs formed by a controllable method exhibit great potential to be used in the future photovoltaic industry as surface texture.